2014
DOI: 10.1007/s13592-014-0318-x
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses of honeybees and their fitness costs as compared to bumblebees

Abstract: Immune responses of invertebrates imply more than developing a merely unspecific response to an infection. Great interest has been raised to unveil whether this investment into immunity also involves fitness costs associated to the individual or the group. Focusing on the immune responses of honeybees, we use the well-studied insect bumblebee for comparison. Bumblebees are capable of producing specific immune responses to infections whereas this has not been assessed for honeybees so far. We investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Also noteworthy is that we only found a difference relating to the immune response of challenged larvae across the gradient of genetic diversity and that there were no differences in the baseline immune production in unchallenged larvae. Since a high constitutive production of antimicrobial peptides can have costs for both individuals and colonies [13,16], selection may favour inducible expression rather than constitutive expression. A recent study has in fact shown that constitutive expression does not seem to correlate with subsequent ability to fight pathogen exposure [22], which supports the findings presented here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also noteworthy is that we only found a difference relating to the immune response of challenged larvae across the gradient of genetic diversity and that there were no differences in the baseline immune production in unchallenged larvae. Since a high constitutive production of antimicrobial peptides can have costs for both individuals and colonies [13,16], selection may favour inducible expression rather than constitutive expression. A recent study has in fact shown that constitutive expression does not seem to correlate with subsequent ability to fight pathogen exposure [22], which supports the findings presented here.…”
Section: Discussionmentioning
confidence: 99%
“…It still remains unclear, therefore, if individuals from colonies with increased genetic diversity differ in their ability to mount an effective immune response after a pathogen challenge. This is a critically important distinction, given demonstrated colony-level fitness costs for individuals' upregulation in immune response [13], as well as costs at the individual level [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an increase in hemolymph antimicrobial activity after immune challenge has been reported in solitary insects such as Galleria mellonella [ 65 ], Musca domestica [ 66 ] and Schistocerca gregaria [ 67 ], as well as in social insects. For instance, it has been reported that Bombus terrestris [ 68 ] and Apis mellifera [ 69 ] bee workers challenged by bacterial-associated molecular patterns showed an increase in hemolymph antimicrobial activity compared to the control or uninfected group. Furthermore, Camponotus fellah worker hemolymph has no antimicrobial properties but it acquires such properties after a trauma [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another cost of immune activation could be the elimination of beneficial microflora from the gut of honey bees (Gilliam, 1997). Riessberger-Gallé et al (2015) provided experimental evidence that the cost of using the immune system reduces survival in immunechallenged bees as compared to control bees. In response to endogenous bacteria, honey bees activate their immune system by upregulating immunity-related genes, but at the same time, the gene-encoding storage protein (Hexamerin 70b) is downregulated (Janashia & Alaux, 2016).…”
Section: Using Immune System Itself Reduces Host Fitnessmentioning
confidence: 99%